2005
DOI: 10.1111/j.1365-294x.2005.02455.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdiversity of ectomycorrhizal fungus assemblages on oak seedlings in mixed forests in the southern Appalachian Mountains

Abstract: Diversity of ectotrophic mycobionts on outplanted seedlings of two oak species (Quercus rubra and Quercus prinus) was estimated at two sites in mature mixed forests in the southern Appalachian Mountains by sequencing nuclear 5.8S rRNA genes and the flanking internal transcribed spacer regions I and II (ITS). The seedlings captured a high diversity of mycorrhizal ITS-types and late-stage fungi were well represented. Total richness was 75 types, with 42 types having a frequency of only one. The first and second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 38 publications
(37 reference statements)
6
68
2
3
Order By: Relevance
“…The most abundant and most frequent species of ectomycorrhizas associated with oaks on serpentine soils were the very common fungal species associated with oaks on all soils world wide: C. geophilum, an asexual Ascomycota with sclerotia; hypogeous Ascomycota (Tuber, Genea, Gilkeya, and other Pezizales); crust-forming resupinate Basidiomycota (Sebacina Avis et al 2003;Valentine et al 2004;Moser et al 2005;Richard et al 2005;Walker et al 2005;Frank et al 2006b). Serpentine soils supported extensive mycorrhizal communities.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant and most frequent species of ectomycorrhizas associated with oaks on serpentine soils were the very common fungal species associated with oaks on all soils world wide: C. geophilum, an asexual Ascomycota with sclerotia; hypogeous Ascomycota (Tuber, Genea, Gilkeya, and other Pezizales); crust-forming resupinate Basidiomycota (Sebacina Avis et al 2003;Valentine et al 2004;Moser et al 2005;Richard et al 2005;Walker et al 2005;Frank et al 2006b). Serpentine soils supported extensive mycorrhizal communities.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, molecular studies revealed hyperdiverse ECM assemblages associated with both Californian (Morris et al 2008;Smith et al 2007;Walker et al 2005) and European (Azul et al 2010;Richard et al 2005) Mediterranean oaks, but most of this research was carried out in forest systems characterized by low disturbance rates or by only ancient disturbance. None dealt with anthropogenic coppices, despite the dominance of this vegetation type in the Mediterranean area.…”
Section: Handling Editor: Jean Garbayementioning
confidence: 99%
“…The dominance of one or a few ECM organism types is a common pattern observed in extreme environments. A few types of ECM organisms, in comparison with some hyper-diverse ECM organism systems such as oak seedlings have also been observed on several other spruce species (Walker et al, 2005), for example, on partially cut Picea glauca trees from natural stands (Lazaruk et al, 2005) and on mature P. abies trees growing in forests with dolomite lime soils in otherwise optimal spruce habitats (Jonsson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%